The abuse potential of carbamazepine: a case report - İnanç, Leman and Altıntaş, Merih and Yazla, Ece (Journal of Dependence, 2016)
Carbamazepine is used for reduction of aggression associated with psychiatric disorders. Carbamazepine is not widely known or recognized as a drug with abuse or misuse potential. In our literature search we have encountered only one case report about the abuse potential of carbamazepine. Here we report a case of carbamazepine misuse we encountered in Turkey. We speculate that the patient’s usage seems to have started with misuse and proceeded into abuse of the medicine. This case study points at a possibility of misuse and perhaps even a risk of abuse of Carbamazepine..